Decoding the Knowledge Sharing Culture and Practices among Librarians in Research Institutions: A Phenomenological Study - Zakir Khan; Dr. Rahim Jan; Izhar Muhammad; Nasir Farid; Muhammad Shahab (Dialogue Social Science Review (DSSR), 2025)
Using a phenomenological methodology to highlight librarians' real-life involvements, perceptions, and interferences, this study investigates into the knowledge-sharing culture and practices in research institutions. Skill in knowledge sharing has grown in prominence in today's information-driven, fast-paced work situation. Institutional performance is dependent on the generation, management, and practice of information. This study appearances at how research libraries substitute an environment favorable to information sharing by analysing the effects of organisational standards, relational undercurrents, technology resources, and specialized principles. Detailed qualitative data was resulting from semi-structured interviews with a wide-ranging group of librarians from several research organizations, shedding light on the complications of partnership undercurrents. Outcomes show that people are usually willing to effort together, but that around are a number of social, technological, and organizational hindrances that avert them from exchanging information as efficiently as they might. Issues such as time limits, diverse points of transparency and expectation, insufficient digital infrastructure, and ranked decision-making are amongst these. The study recommends that in instruction to advance institutional learning, there should be more governance commitment, programmes for continuing professional growth, and the use of cutting-edge digital stages for sharing information. Libraries in research-intensive backgrounds can advance their cooperative capability and agility by addressing these restraints and building inclusive, supportive philosophies. This research enhances to the current form of literature on library knowledge organization by providing theoretic backgrounds and applied recommendations for building information-sharing principles that can withstand challenges. Keywords: Knowledge-sharing culture, librarians, research institutions, phenomenology, knowledge management.